2017
DOI: 10.19082/5199
|View full text |Cite
|
Sign up to set email alerts
|

The pedagogical effect of a health education application for deaf and hard of hearing students in elementary schools

Abstract: BackgroundDeaf or hard-of-hearing children experience difficulties in learning health principles. But technology has significantly improved their ability to learn. The challenge in e-learning is to design attractive applications while having an educational aspect.ObjectiveThe aims of this study were to determine the pedagogical effectiveness of a health education application for deaf and hard of hearing students in elementary schools, and to investigate the student’s perceptions in different educational grades… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 12 publications
0
8
0
1
Order By: Relevance
“…The video was another technology present in the studies. It allows the use of several simultaneous and playful resources and favors the construction of mental images or visual association, enabling learning, memorization and construction of specific skills 40 . All the studies included in this review, using this type of technology, indicated its effectiveness in the intervention 19-22 .…”
Section: Discussionmentioning
confidence: 99%
“…The video was another technology present in the studies. It allows the use of several simultaneous and playful resources and favors the construction of mental images or visual association, enabling learning, memorization and construction of specific skills 40 . All the studies included in this review, using this type of technology, indicated its effectiveness in the intervention 19-22 .…”
Section: Discussionmentioning
confidence: 99%
“…In particular, videos for educational purposes promote the quality of teaching and learning, increase the willingness to learn, memorize and conduct specific teaching skills. 13 For the deaf, accessible videos are appealing to education because they allow the use of a number of simultaneous and playful resources that stimulate learning and enable the use of sign language. 38 In addition, the use of videos in health education activities contributes to the assistance and communication of the information of the non-proficient professional in sign language and to the dissemination of information in mass and in places where professionals do not arrive/are not present.…”
Section: Discussionmentioning
confidence: 99%
“…These advantages are corroborated by results of a study carried out in Iran, with 82 deaf teenagers, which identified that the use of information technology can statistically improve the learning achievement of deaf students. 13 Thus, the process of training, guidance and information is a right of deaf people and presents itself as a challenging demand for professionals who work with health education. In order to cope with this problem, the studies indicate that the use of printed, computer-mediated or video technologies contributes to the effectiveness of health education with deaf people, as long as they are adapted to the communication and understanding of this community.…”
Section: /14mentioning
confidence: 99%
“…The healthcare staff is not so aware of the issues that deaf children face due to their communication skills problems. [6][7][8][9] The World Health Organization supported the promotion of oral health, in 1989, as an integral part of health actions for all, and the Fifth International Conference on Health Promotion was carried out in Mexico City with the central theme "Bridging the equity gap". 10,11 During Mexico Day, the session was dedicated to showcasing a range of Mexican experiences of health promotion as a crosscutting approach applied to disease prevention.…”
Section: Introductionmentioning
confidence: 99%